2017
DOI: 10.1111/joa.12655
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral column regionalisation in Chinook salmon, Oncorhynchus tshawytscha

Abstract: Teleost vertebral centra are often similar in size and shape, but vertebral-associated elements, i.e. neural arches, haemal arches and ribs, show regional differences. Here we examine how the presence, absence and specific anatomical and histological characters of vertebral centra-associated elements can be used to define vertebral column regions in juvenile Chinook salmon (Oncorhynchus tshawytscha). To investigate if the presence of regions within the vertebral column is independent of temperature, animals ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 93 publications
3
54
1
Order By: Relevance
“…This study subdivides the vertebral column into six regions (regions I–IV) to analyse the effect of temperature on meristic characters. These regions have been described in detail previously (De Clercq et al, ) and are shown in Figure . Briefly, the postcranial (I) region comprises the first vertebrae that lack ribs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study subdivides the vertebral column into six regions (regions I–IV) to analyse the effect of temperature on meristic characters. These regions have been described in detail previously (De Clercq et al, ) and are shown in Figure . Briefly, the postcranial (I) region comprises the first vertebrae that lack ribs.…”
Section: Methodsmentioning
confidence: 99%
“…Regionalization of the Chinook vertebral column. Schematic representation of the vertebral column regions in Chinook salmon described in the work of De Clercq et al (). The subtype transitional vertebrae are abbreviated with IIIa, IIIb, IIIc, and IIId.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, hyper radio-dense vertebral bodies have been linked to P deficiency (Helland et al, 2006). Teleost vertebral bodies are composed of vertebral centra and associated structures (arches, spines and ribs), described in detail for Pacific salmon (De Clercq et al, 2017). Centra consist of two conical vertebral body endplates (horizontal hourglass), spongy bone between the endplates and notochord tissues in the intervertebral space (Laerm, 1976) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Elements associated with the vertebral centra are parapophyses, ribs, neural and haemal arches, neural and haemal spines, and the caudal fin skeletal elements (Arratia et al., ). Except neural and haemal spines which ossify intramembranously, associated elements derive from the somites (sclerotome), and in salmonids develop as cell‐rich hyaline cartilaginous anlagen before perichondral and endochondral ossification starts (Arratia et al., ; de Azevedo et al., ; De Clercq et al., ; Grotmol, Kryvi, Nordvik, & Totland, ; Huxley, ; Kölliker, ; Schaeffer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Except neural and haemal spines which ossify intramembranously, associated elements derive from the somites (sclerotome), and in salmonids develop as cell-rich hyaline cartilaginous anlagen before perichondral and endochondral ossification starts (Arratia et al, 2001;de Azevedo et al, 2012;De Clercq et al, 2017;Grotmol, Kryvi, Nordvik, & Totland, 2003;Huxley, 1859;K€ olliker, 1859;Schaeffer, 1967).…”
mentioning
confidence: 99%